Barrels XXVII meeting report: Barrels in the monument city. (3rd July 2015) - Bajnath, Adesh; Chu, Philip; Steger, Robert; Brumberg, Joshua C.
Abstract: The 27th annual Barrels meeting highlighted the latest advances in this rapidly growing field. The Barrels meeting annually focuses on the role of the posterior medial thalamus in somatosensation, dendritic processing, and the cortical dynamics involved during touch perception. Speakers utilized diverse molecular, physiological, computational techniques to understand the development, sensory processing, and motor commands that are involved with the rodent mystacial vibrissae. The meeting was held Thursday, 13 November through Friday, 14 November 2014 on the Homewood campus of Johns Hopkins University, Baltimore, MD.